Analytical Study on the Influence of Parasitic Elements in a Memristor. (7th March 2018) - Chandía, Kristopher J.; Bologna, Mauro; Tellini, Bernardo
Abstract : We study a memristive circuit with included parasitic elements, such as capacitance and inductance. In the multiple-scale scheme, we analytically show how the parasitic elements affect the voltage and the current. Finally, we provide an analytical expression for the intersection point coordinates, through which we discuss the functional behavior of the pinched hysteresis loop versus the operating frequency and the parasitic elements.